Relevant technical aspects in the treatment surgical treatment of cardiopericardial wounds: 9 years of experience at Hospital Pasteur - Villanueva, Oscar; Campos, Alejandro; Villarino, Alicia; Maggiolo, José; González, Fernando; Croci, Fabio (Cirugía del Uruguay, 2006)
lntroduction. Penetrating cardiac traumatism is rare, but it is of extreme importance as it is associated to high morbimortality. lt represents a diagnostic and therapeutic chal/enge. Most patients die befare they get to hospital but those that do arrive while sti/1 alive have a high survival rate. Obiectives. The purpose of this paper is to revise current trends in operative management of cardio-perdicardiac wound as we/1 as analyzing our experience in the treatment of such patients. Design. Decriptive and retrospective analysis. Population. Thirty-three patients with operated cardio-perdicardiac wounds in the period 09/1995 thróugh 09/2004. Method. Data compi/ation recording demographic variables; mechanism and lesion topography; lesion evaluation: approach; treatment and mortality. Results. Patients treated were 33 o ver a 9-year period: 42% in the two-year period 2001-2002; 82% were male. Average age: 28 years old (16 to 48);